2012
DOI: 10.1111/j.1365-2702.2012.04217.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐transcendence and nurse–patient interaction in cognitively intact nursing home patients

Abstract: Caring behaviour signifies the vital and ultimate qualitative nursing behaviour, which promotes self-transcendence and thereby well-being. These findings are important for clinical nursing that intends to increase patients' well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 47 publications
(91 reference statements)
5
81
0
8
Order By: Relevance
“…Other studies on ST and depression have consistently found that lower STS scores are associated with depression (e.g. Ellermann & Reed, 2001;Kausch & Amer, 2007) in independent-living older people (Reed, 1991b) and in older nursing homes residents (Haugan, Rannestad, Hammervold, et al, 2012;Haugan, Rannestad, Hanssen, et al, 2012). In a study among older Taiwanese people living in nursing homes, a low degree of ST had the strongest association with depressive symptoms (Hsu, Badger, Reed, & Jones, 2013).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Other studies on ST and depression have consistently found that lower STS scores are associated with depression (e.g. Ellermann & Reed, 2001;Kausch & Amer, 2007) in independent-living older people (Reed, 1991b) and in older nursing homes residents (Haugan, Rannestad, Hammervold, et al, 2012;Haugan, Rannestad, Hanssen, et al, 2012). In a study among older Taiwanese people living in nursing homes, a low degree of ST had the strongest association with depressive symptoms (Hsu, Badger, Reed, & Jones, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Enabling wellbeing and ST in older frail people places demands on the ability of caregivers and family members to be open and aware as well as on their moral sensitivity and responsiveness. The interaction between caregivers and older people has been shown to have a positive impact in cognitively intact older people living in nursing homes (Haugan, Rannestad, Hammervold, et al, 2012;Haugan, Rannestad, Hanssen, et al, 2012). Kirkevold (2005, 2006) have studied the importance of thriving for older nursing home residents, and they showed the importance of the caregivers' ability to facilitate and shape meaningful interactions in allowing the very frail older residents in nursing homes to thrive (Bergland & Kirkevold, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…La disciplina de enfermería puede actuar en sinergia (como un factor moderador y mediador) durante el proceso de autotrascendencia en el adulto mayor. La relación que tienen los profesionales de la salud con este mecanismo adaptativo es de gran relevancia, ya que pueden favorecer el desarrollo de la autotrascendencia en 12 .…”
Section: Nivel De Autotrascendencia En Un Grupo De Adultos Mayores Meunclassified
“…Esto se relaciona con otros estudios en donde la autotrascendencia intrapersonal se encuentra mayormente elevada que la interpersonal y estrechamente relacionada con el aspecto espiritual mejorando en gran medida el bienestar espiritual expresado 7,11,13,25 , dicha relación con la espiritualidad se ve manifestada en el significado de las creencias y además como señalan otros estudios esto se expresa a través de la participación en los rituales y la necesidad de tener momentos de serenidad, paz y contemplación 12 . Aquellos adultos mayores que participan más asiduamente de sus creencias en sus prácticas tienen mejor nivel de autotrascendencia 23 , lo que sigue ligando a este proceso la parte espiritual del ser humano.…”
Section: Nivel De Autotrascendencia En Un Grupo De Adultos Mayores Meunclassified